KOMPETENSI MANAJERIAL KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU - Pujiono; Zuroyda, Chofifatin (AN NAHDLIYYAH, 2025)
Management is a very important factor in the administration of a madrasah, which includes planning, organizing, implementing, and evaluating. In the development of a madrasah, the role of the principal can not be separated, as the principal serves as the main leader within the organization. However, the principal cannot carry out this task alone without the support of teachers, since teachers play an active role in the teaching and learning process. Therefore, the principal’s duty is to improve the quality of teacher performance. Based on the background above, the focus of this study includes (1) The application of managerial competence by the principal in improving teacher performance, (2) The principal’s efforts in enhancing teacher performance, and (3) The supporting and inhibiting factors faced by the principal in improving teacher performance. The researcher chose MTs NU Karangploso Malang as the research site because the institution aligns with the focus of the study. This research uses a qualitative approach, with data collected through participant observation, in-depth interviews, and documentation. The results of the study at MTs NU Karangploso Malang show that the principal has implemented managerial functions effectively. The efforts made by the principal to improve teacher performance include involving teachers in training or workshops, enforcing discipline in teaching schedules, and fostering good cooperation and communication. The supporting factors for improving teacher performance include a comfortable and conducive school environment, while the inhibiting factor is the lack of facilities and infrastructure within the madrasah.